"Nano" Regeneration: How Human Agency Intermediates Between Nature and Technology in Community-Based Energy. (December 2021) - Walther, Charlotte Marie; Poldner, Kim; Kopnina, Helen; Dentoni, Domenico
This article provides a nano (hyperlocal) view of climate change mitigation by viewing regenerative organizing through the eyes (as well as bodies and senses, etc.) of the households engaged in community-based energy projects. By showing what humans make up for in the largely absent relationship between nature and technology in these projects, we envision an incremental extension of the literature on community-based energy. The radically different contribution we aim to make is a tripartite imbrication that brings in natural agency alongside the human and the technical but specifies precisely how nano (smaller than micro) embodied practices afford mis- and realignments.